ANALYSIS OF THE EFFECT OF IMPLEMENTING DRIVING MONITORING SYSTEM ON HAZARDOUS INCIDENTS, ACCIDENTS, AND PERFORMANCE OF DUMP TRUCKS AT PT ABC - Setyo Wicaksono, Ferdy
PT ABC implemented Driving Monitoring System (DMS) technology for direct supervision of dump truck operation behavior (driver activities inside the cabin and external conditions) to prevent accidents and hazardous incidents. Notifications reported by the DMS include driver behaviors such as Fatigue (yawning, head down, closed eyes), Distraction (smoking, using gadgets), Overspeed, Over Idle, and Over Parking. This research aims to determine the effect of using the Driving Monitoring System on accident rates, hazardous incidents, production, and equipment performance. The research results show that hazardous incidents decreased by 57.89%, accidents decreased by 66.67%, limestone and clay production decreased by 19%, and productivity decreased by 28.62%. The performance of SCANIA P360CB-6x4 dump trucks experienced a decrease of 6.24% for PA, 0.90% for UA, 7.26% for MA, and 4.10% for EU. Quester CWE-37064R dump truck experienced an increase of 4.64% for PA, a decrease of 3.59% for UA, an increase of 3.51% for MA, and a decrease of 0.73% for EU. ISUZU FVZP34P004L2S dump truck experienced a decrease of 38.92% for PA, a increase of 3.36% for UA, a decrease of 42.18% for MA, and a decrease of 3.04% for EU.